Esophageal replacement in children: A 10-year, single-center experience - Mongkol Laohapensang (2020)
© 2019 Siriraj Medical Journal. Objective: Various esophageal replacement grafts have been used in children, although none can equal the native esophagus. The purpose of this study was to review the complications and outcomes associated with using different techniques in a single institute. Methods: A retrospective medical record review was conducted from 2006 to 2016. Patient demographics, perioperative clinical courses, complications and long-term outcomes were reported as percentages and categorized according to the surgical procedure performed. Results: A total of 15 children underwent esophageal replacement procedures, comprising 7 (47%) isoperistaltic gastric tubes, 3 (20%) colonic interpositions, 3 (20%) gastric transpositions and 2 (13%) reversed gastric tubes. Indications for esophageal replacement included long-gap esophageal atresia (5; 33%), esophageal atresia with severe postoperative complications (6; 40%), and caustic injury (4; 27%).The mean age of patients was 2.9 years (range: 0.2-15 years). The average follow-up duration was 3.6 years (range: 0.4-8 years). There was no perioperative mortality and no graft loss in any group. The long-term outcomes were acceptable, with no late stricture. Eightysix percent of the patients in the isoperistaltic gastric tube group and all patients in the other procedural groups achieved full oral feeding. Nevertheless, the patients had various degrees of malnutrition. Conclusion: Esophageal replacement remains a major challenge in children. Our experience indicates that children can be safely operated on using any of these methods, with acceptable outcomes and no deaths. Nevertheless, the long-term consequences and complications should be monitored throughout adulthood.